Understanding the Sustainability of Business Turnarounds: The case of Taylor Wimpey - Bhaskaran, Sabarinath (2012)
Much of the extant turnaround literature focusses on the actions taken by firms to turnaround decline although actions tend to be objective and not specific to distinct turnaround situations. The lack of focus on decline, however, is certainly not encouraging given that it is a common factor in all turnaround cases. Declines and turnarounds are a regular occurrence which leads this research to question the sustainability of turnarounds. The scenario where firms slip back into decline after turnaround is a case of turnaround reversal and it could mean that they have not addressed the causes for decline properly or have not been able to adapt to new changes in the market and/or industry. This research attempts to understand turnaround reversals and its causes by applying an exhaustive case research method. A robust case selection methodology was applied to FTSE All Share companies and Taylor Wimpey was selected for detailed case analysis. The case study proceeded to examine three distinct phases in Taylor Wimpey’s history covering a period of 20 years (fiscal years 1992 – 2011) supported by a wealth of primary and secondary data on the company. With the application of contemporary turnaround processes such as restructuring, mergers and acquisitions, strategic leadership, repositioning, refocusing and diversification this study was able to understand turnaround reversals and the gain valuable insight into the sustainability of turnarounds. This study also hopes to be the stepping stone to further studies on turnaround sustainability and reversals.